The inevitability of automobility: How private car use is perpetuated in a greenfield housing estate - Kent, Jennifer L. (Journal of Transport and Land Use, 2022)
Ongoing advances in technologies of connectivity have strengthened our capacity to envision urban environments less dominated by private car use. Yet many cities remain attached to, and defined by, the automobile. In challenging this status quo, we must understand the complex and varied ways private car use is reinforced in different urban environments. This paper provides such an understanding in the context of a low-density, and currently car-dependent, city. It presents a detailed analysis of the system of automobility to demonstrate the way private-car use is unintentionally perpetuated through contemporary practices of planning, developing and inhabiting cities. A newly constructed suburb in Sydney, Australia, provides the case for analysis. The suburb—Oran Park—is a master-planned estate intentionally designed to encourage alternative transport modes that is rendered ostensibly car-dependent as a result of a confluence of historical and contemporary structural and practical influences. The paper combines a detailed examination of the planning, transport and land-use context of the suburb with survey data from 300 of its residents. The paper’s novel contribution is to analyze these data sources using a social practice approach. The analysis lays bare the inevitability of automobility’s reproduction in the estate—describing the litany of elements that are both infrastructural and cultural and that, in orchestration, reproduce private car use. These elements are deconstructed to inform future challenges to the hegemony of the private car.